Heat transfer of advanced coolant dispersed with hybrid oxides nanoparticles in PEMFC cooling plates / Saifuddin Khalid @ Chik - Khalid @ Chik, Saifuddin (2020)
Thermal management analysis has always been a major concern in the energy-based sector. Thermal management in Proton Exchange Membrane Fuel Cell (PEMFC), as one of the leading green energy converter, is extremely important to ensure efficient heat extraction from the system. The low operating temperature of PEMFC has been known to reduce the rate of heat transfer which contribute to large volume space consumption for the cooling mechanism. The low electrical conductivity requirement of the system also limited the implementation of the well-established nanofluids as a coolant in PEMFC. This research aims to study the effect of hybrid nanofluids Al2O3-SiO2 with 0.5% volume concentration dispersed in base fluid water to heat transfer enhancement in PEMFC. Nine different ratios of hybrid Al2O3-SiO2 nanofluids were investigated, starting from 10:90 (Al2O3:SiO2) to 90:10. Three thermophysical characteristics affecting heat transfer of fluids were analyzed namely thermal conductivity, electrical conductivity and dynamic viscosity of each sample. Correlation between properties was investigated using property enhancement ratio (PER) of thermo-electrical and thermo-hydraulic of each sample. Investigations made on two different cooling plates which are Serpentine-type and Distributor-type to obtain Nusselt number and pumping power requirement through the adoption of hybrid nanofluids in PEMFC. At the end of the experiment, the most feasible nanofluids ratio and cooling plate type for PEMFC application was selected. The Al2O3-SiO2 hybrid nanofluids with ratio R1 (10:90) is shown as the most prominent ratio among all samples of Al2O3-SiO2 hybrid nanofluids. Ratio R1 (10:90) exhibits the highest convective heat transfer coefficient and Nusselt number but show higher pumping power requirement as compared to the other ratios. Serpentine-type cooling plate shows the most feasible cooling plate with the highest convective heat transfer and Nusselt number at all ratios. It also shows a lower value in pumping power as compared to Distributor-type plate.